2016
DOI: 10.1109/tifs.2016.2585086
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Deniably Authenticated Encryption and Its Application to E-Mail

Abstract: Confidentiality and authentication are two main security goals in secure electronic mail (e-mail). PGP and S/MIME are two famous secure e-mail solutions. Both PGP and S/MIME use digital envelope to provide message confidentiality and digital signature to provide message authentication. However, these methods have the following two weaknesses: (1) digital signature provides non-repudiation evidence of sender that is not desired in some e-mail applications; (2) efficiency is low since these methods use two kinds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…For example, our scheme is aimed at application scenarios we discuss in the section of introduction. By comparing our scheme with the latest scheme [18], it is found that both of two schemes have the same security features but our scheme has less computational overhead and shorter ciphertext length. The computational complexity of modular multiplication operation is much higher than other operations in the scheme.…”
Section: Theoretical Analysis and Experimentsmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, our scheme is aimed at application scenarios we discuss in the section of introduction. By comparing our scheme with the latest scheme [18], it is found that both of two schemes have the same security features but our scheme has less computational overhead and shorter ciphertext length. The computational complexity of modular multiplication operation is much higher than other operations in the scheme.…”
Section: Theoretical Analysis and Experimentsmentioning
confidence: 97%
“…Yongjian et al [17] constructed a protocol using a secure certificateless signature scheme and outsourcing the verification of signature to a cloud server. Li et al [18] introduced a new concept called deniable authenticated encryption.…”
Section: A Related Workmentioning
confidence: 99%
“…Li et al [ 31 ] constructed a DAE scheme with formal security proof. They also constructed an email system based on the designed DAE scheme.…”
Section: Related Workmentioning
confidence: 99%
“…Later, Hwang et al [19] constructed a non-interactive (NIA) DAP that supports both fair protection and anonymity. Li et al [20] designed a DAE scheme. They provide an example of how to apply their proposed DAE scheme to e-mail systems.…”
Section: Related Workmentioning
confidence: 99%